Restructuring the State through Economic and Trade Agreements: The Case of Investment Disputes Resolution - Finbow, Robert G. (2016)
This essay will examine the emergence of transnational governance via supranational economic agreements which promote global imposition of liberalizing policies in the interests of transnational investors. The stalled multilateral World Trade Organization (WTO) process has given way to a plethora of regional and bilateral economic agreements covering a range of new issues—investment, intellectual property, services, and regulations—which trench ever more deeply on domestic decision-making. Informed by Phillip Cerny’s conception of “competition states”, Colin Crouch’s (2000) lament about “post-democracy”, Carroll and Sapinski’s analysis of “global corporate elites”, and David Held’s depiction of “global governance complexes”, the essay will examine the role of transnational corporate and institutional elites in advancing economic agreements which narrow the scope for democratic governance. These authors depict the combination of constraint and empowerment of states induced by these transnational agreements which force most liberal democracies to cut or tweak programs and regulations in economic and social fields to protect investor rights, while boosting restraints on citizens in areas like intellectual property—what Cerny (1997) calls the “paradox” of the competition state. Given the number and complexity of these transnational governance arrangements, this essay will focus on the transnational constraints of investor state arbitration and disputes settlement systems. This will be illustrated by examining the growth of investor disputes settlement claims in bilateral treaties and major European and North American economic agreements and the rise of arbitration cases which impose costs on states for violations of investor rights. The essay considers the implications of these new forms of transnational governance for democratic governments’ responsive to popular demands. It concludes by suggesting the need for revisions to theories of the democratic state, which may be morphing into pluralistic plutocracy.